Afiksasi Verba Bahasa Madura Dialek Pamekasan berdasarkan Perspektif Derivasi dan Infleksi - Holifatul Hasanah; Eti Setiawati; Ika Nurhayani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe the affixation of Madurese verbs in the Pamekasan dialect of low speech level based on the perspective of derivation and inflexion. The data of this research is in the form of Pamekasan dialect Madurese verbs. The data sources in this study were 10 informants who were native speakers of the Pamekasan Madura dialect, which were determined using the snowball sampling technique. Data collection is done by using the interview method with elicitation techniques. The data obtained were then analyzed through three stages: the data reduction stage, the data presentation stage, and the conclusion preparation stage. The results showed three processes of verb-forming affixation in the Pamekasan dialect of Madura, including prefixation, suffixation, and confixation. Based on the data, it was found that several affixes that make up Pamekasan dialect Madurese verbs, including prefixes ma–, a–, ta–, N–, –, pa–, pa–, nga–, and ka–, suffixes –a, – aghi, and –è, and the confixes a–aghi, N–aghi, N–è, ma–aghi, –aghi, ma–ana, –è, a–an, ma–è, and ma–an. This affixation is divided into inflectional affixation, transpositional derivational affixation, and non-transpositional derivational affixation.